Physicochemical properties of three sugary cassava landraces - Souza,Hugo Antonio Lima de (2013)
This study evaluates the physical and physicochemical properties of three sugary cassava (Manihot esculenta Crantz) landraces: São Francisco Bag 3, Manicueira 62, and Castanhal Iracema. These three landraces showed high estimated productivity (≥3.93kg plant-1) and had a high sugar content (≥3.92g 100g-1 of root), making them viable for use in syrup production, especially the São Francisco Bag 3 landrace (4.76g 100g-1). The Manicueira 62 landrace had the highest starch content (4.40g 100g-1). The three sugary cassava landraces exhibited high levels of cyanide (>195mg kg-1), indicating the need for processing prior to consumption.